Growth, Total Production and Feed Efficiency of Catfish (Clarias sp.) Orally Administered with Shrimp Waste Hydrolyzate - Hariyadi, Dimas Rizky; Isnansetyo, Alim; Istiqomah, Indah; Hardaningsih, Ign.; Wahyudi, Wahyudi; Kim, Sung Sam (Indonesian Aquaculture Society (MAI), 2018)
Shrimp Waste Hydrolyzate (SWH) /Shrimp Soluble Extract (SSE) is a product produced from the enzymatic process of shrimp waste. SWH contains essential and non-essential amino acids which useful for fish. This study aimed to determine effect of SWH on the growth and total production of catfish. The parameters observed were average growth rate, specific growth rate (SGR), food conversion ratio (FCR), protein efficiency ratio (PER), total production and length weight relationship from beginning until the end of rearing period. Growth performance was observed by calculating average growth rate and SGR of catfish. The results of this study showed that oral administration of SWH significantly increased SGR of catfish length at 4th sampling period with value 1.54% body length/day. Administration of SWH did not affect on the AGR, FCR, PER and total production. The growth pattern of catfish is negative allometric.